Reception Of Followers Towards Books Review Content As Digital Promotion Media (Case Study From Tiktok Social Media Account @raniadevina) - Mutiara, Natasha; Nabila, Jeihan (Departemen Informasi Perpustakaan dan Kearasipan, 2025)
Abstract This research aims to describe how followers receive book review content as a digital promotional medium (case study of the TikTok social media account @raniaadevina). This research was conducted using qualitative research methods with a case study type of research. Data was collected through in-depth interviews with followers of the TikTok account @raniadevina. The theory used in this research is the AISAS theory, which emphasizes the flow of consumer behavior in the digital era. Based on research results, book review content on Tiktok social media can be an effective digital promotional medium if it is presented in a way that is interesting and relevant to the target audience. The TikTok account @raniadevina has succeeded in building strong connections with followers through quality book review content, thus being able to influence its followers' book purchasing decisions. Keywords: Followers reception, book review content, digital promotion media